Influence of socio-demographic factors on medicinal plant knowledge among three selected ethnic groups in south-central Ethiopia - Sintayehu Tamene; Mesele Negash; Fortunatus Bulabo Makonda; Linley Chiwona-Karltun (BMC, 2024)
Abstract Background The influence of socio-demographic variables was widely explored to evaluate their impact on indigenous and local ethnobotanical knowledge. However, the studies conducted in Ethiopia mainly focused on rural areas. They were limited to exploring and documenting ethnobotanical knowledge and the associated impacts of socio-demographic variables in rural-urban interface areas among ethnic groups. Hence, this study aimed to document plant-based indigenous and local ethnomedicinal knowledge and the associated impacts of socio-demographic variables among selected three ethnic groups in south-central Ethiopia. Methods Ethnobotanical data were collected using semi-structured interviews with 189 key informants, floristic species inventories, and field observations. Quantitative approaches were used to evaluate the use values (UV) of the most important medicinal plants, the informant consensus factor (ICF), fidelity level (FL), relative popularity level (RPL), and rank-order priority (ROP). Statistical tests were applied to evaluate the influences of socio-demographic factors and associations between variables on local ethnobotanical knowledge across ethnic groups in different informant categories. Results Statistical analysis revealed significant differences (p < 0.05) in the mean number of medicinal plants reported among age categories. There was also a positive association between the respondent's age and plant knowledge acquisition. Croton macrostachyus Hochst. ex Delile, Albizia gummifera C.A.Sm., Zingiber officinale Roscoe, Aloe macrocarpa Tod., Gymnanthemum amygdalinum (Delile) Sch.Bip., Calpurnia aurea (Aiton) Benth, and Allium sativum L. had the highest use values among ethnic groups. The highest informant consensus factor values were recorded for circulatory system disorders (0.68) followed by febrile illness and reproductive organ complications (0.66 each) across the three studied ethnic groups. The highest FL, RPL, and ROP values were noted for Lactuca inermis Forssk., Moringa stenopetala (Baker f.) Cufod., Withania somnifera (L.) Dunal, Allium sativum L., Citrus limon (L.) Osbeck, Ricinus communis L., Schinus molle L., Antiaris toxicaria (J.F.Gmel.) Lesch., Brucea antidysenterica J.F.Mill., Echinops kebericho Mesfin, Ocimum jamesii Sebald, Afrocarpus falcatus (Thunb.) C.N.Page, Searsia natalensis (Bernh. ex Krauss) F.A.Barkley, and Ricinus communis L. across ethnic groups in the study areas, which showed the conformity of knowledge on species curing potential and their prevalent uses. Conclusion The study revealed that the ethnic groups of Gedeo, Oromo, and Sidama have considerable indigenous and local ethnobotanical knowledge practices. Statistical analysis shown high variation in the acquisition of local ethnobotanical knowledge among age groups, which boosted our understanding of the effects of socio-demographic factors on the local ethnobotanical knowledge dynamics. Thus, this finding advocates for efforts to repair the observed generation gap via continued professional support and educating local communities to preserve traditional knowledge and practices through systematic documentation.